Transnationalism, activism, art - Dobson, Kit, 1979-; McGlynn, Áine (University of Toronto Press, 2013)
"Banksy is known worldwide for his politically subversive works of art, but he is far from the only artist whose creations are infused with internationally relevant, activist themes. How else can the arts help activate citizen participation in social justice movements? Moreover, what is the role of culture in a globalizing world?